Type 1 Diabetes Mellitus and glyco-oxidation pathways related to hiperglycemi (Research, Society and Development, 2023)
Type 1 Diabetes Mellitus (T1DM) is an autoimmune disease with a prevalent incidence in childhood (approximately 10 to 14 years old), but it can develop at any age. The knowledge regarding the pathophysiology of T1DM is extensive; however, articles addressing the adaptive immune response developed against autoantigens and the oxidative consequences of glucose excess in the body are still necessary. In this literature review, the primary objective was to discuss the pathways of both innate and adaptive immunity activated during the development of T1DM, and following the disease development, the alternative pathways of glyco-oxidation activated due to the excess glucose in the body. Platforms such as PubMed, Science Direct, and Google Scholar were utilized for this purpose. Through understanding these two processes, novel treatment methods might be designed. The mechanisms involved in the generation of reactive oxygen species (ROS) can serve as a valuable tool in the search for new therapeutic targets aimed at reducing the risk of developing secondary pathologies related to T1DM.